The Relationship Between Family Support And Leisure Time Utilization With Mental And Emotional Conditions In Children - Sidrotul Hana; Muhammad Purnomo; Sri Karyati (International Journal of Health and Pharmaceutical (IJHP), 2026)
Children's mental and emotional state is influenced by family support and the use of free time. This study aims to analyze the relationship between these two factors with the mental and emotional state of junior high school students. This quantitative study with a correlational design and a cross-sectional approach involved 284 eighth-grade students as the population and 57 respondents as the sample through two-stage cluster sampling. The instruments included a family support questionnaire, the Leisure Time Activity Questionnaire (LTAQ), and the Strengths and Difficulties Questionnaire (SDQ). Data were analyzed using the Spearman Rho test. The results showed that family support (r = -0.592; p = 0.001) and the use of free time (r = -0.311; p = 0.019) were significantly related to mental and emotional state. In conclusion, increased family support and positive use of free time contribute to better mental and emotional state of children